Host‐microbiota interactions and adaptive immunity. Issue 1 (September 2017) - McCoy, Kathy D.; Ronchi, Francesca; Geuking, Markus B.
Summary: All mucosal surfaces are colonized with a vast number of microbes, which are essential for stimulating and regulating the immune system. While intrinsic and innate mechanisms exist to promote a strong barrier between the microbiota and the host to ensure compartmentalization, the microbiota is also able to induce robust adaptive immunity. In this review, we discuss the interplay between the microbiota and the adaptive immune system, with a focus on the induction of mucosal and systemic antibody responses and newly defined roles of maternal antibodies. We also highlight recent studies that aim to decipher microbial antigen‐specificity of the T‐cell compartment.